Synthesis and drug-release properties of biodegradable hydrogels having beta-cyclodextrin - KAYAMAN APOHAN, NİLHAN (SPRINGER, 2013)
A new beta-cyclodextrin (beta-CD) methacrylated monomer was synthesized from the reaction of beta-CD, glycidyl methacrylate. Based on inclusion character of beta-CD, a series of hydrogels were prepared by irradiating the mixtures of beta-CD methacrylate monomer (beta-CD-Met), poly(ethylene glycol) monoacrylate, poly(ethylene glycol)diacrylate, fumaric acid monoethyl ester-functionalized poly(lactic-co-glycolic) acid, 1-vinyl-2-pyrrolidone, N,N'-methylene bisacrylamide, and the photoinitiator. Gel percentages and equilibrium swelling ratios (%) of hydrogels were investigated. It was observed that equilibrium-swelling ratio increased with increasing beta-CD-Met content in the hydrogel composition. SEM images demonstrated that beta-CD-Met-based hydrogel have lots of voids on the fractured surface. In this study, ibuprofen (IBU) which is capable of forming inclusion complex with beta-CD was chosen. For the hydrogel with maximum CD content, the IBU drug loading was found as 9 mg/g dry gel. It can be concluded that the inclusion complex-formation capability of beta-CD moiety increases the drug release by improving the aqueous solubility of hydrophilic drugs.
Keywords: beta-Cyclodextrin; Ibuprofen; Photoinitiation; Drug release; Inclusion complex; Hydrogel; POLY(ETHYLENE GLYCOL); INCLUSION COMPLEXES; NETWORKS